Peta Pemetaan Luas Area Berdasarkan Jumlah Produksi Tanaman Tembakau Di Kabupaten Rembang Dengan Pendekatan Sistem Informasi Geografis - Chairunnita Chairunnita; Bambang Agus Herlambang (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to map the area of tobacco farming with the amount of tobacco production in Rembang Regency, using a Geographic Information System (GIS) approach. This spatial analysis method allows researchers to understand the geographic pattern of area mapping based on the amount of tobacco production, as well as the factors that influence this mapping. This research involves collecting spatial and non-spatial data, which is then analyzed spatially via GIS software. Non-spatial data on the area of tobacco farming and tobacco production were obtained from various regions in Rembang Regency. Analysis of the results shows that there is a correlation between area size and the amount of tobacco production in various locations. It is hoped that the results of this research can provide in-depth insight into the impact of large tobacco farming areas on tobacco production, provide a basis for sustainable agricultural planning, and serve as a guide for decision making at the regional government level and related institutions.